Effect of test year, parity number and days in milk on somatic cell count in dairy cows of Los Ríos region in Chile - Sebastino, Kiala B.; Uribe, Héctor; González, Humberto H. (Austral Journal of Veterinary Sciences, 2020)
In Chile, most dairy cattle are located in the southern region of the country, where the largest volume of milk is produced. This study aimed to quantify changes of somatic cell count (SCC) over 20 years in 11 herds of the Los Ríos region and to assess the effect of parity number, days in milk, milk yield, and milk fat and protein content on SCC. A database of approximately 277,709 observations based on 10,363 cows from 11 herds of the area was used. Data were gathered from 1998 to 2018. Outliers and inconsistent observations were eliminated. Multiple linear regression was used to model SCC on fixed variables such as test year, parity number, test season, and stage of lactation; covariables included in the model were milk yield, milk fat and protein yields, and milk urea concentration. There were statistically significant associations among SCC and all independent variables included in the model. Regarding parity number and stage of lactation, they increased along with SCC. SCC was higher in warmer months and, as SCC increased, the yield decreased. It was concluded that as test year increased, SCC decreased, indicating that the mammary gland health improved and the quality of the milk was better.